Microsolvation of small cations and anions (2018)
Recent advances in the theoretical treatment of microsolvation of small ions, a problem with practical implications in chemistry, physics, and biology, are exposed. In particular, we discuss sound stochastic approaches to sample complex energy landscapes and delve into the nature of bonding interactions that dictate both structural and energetical preferences. An in-depth analysis of the effect of formal charges in the surrounding network of solvent to solvent hydrogen bonds is also presented. The problem, as expected, is more complicated than simple definitions may forecast. © 2018 Wiley Periodicals, Inc.